The flushing effect and expression of follicle stimulating hormone receptor rariants in sheep. - Hand, Jacqelyn M. (Kansas State University, 2011)
An increase in pre-mating dietary energy positively influences ovulation and lambing rates, and this practice is known as nutritional flushing. The mechanisms of flushing, however, are still unknown. Increasing dietary energy approximately two weeks before breeding likely increases the production of insulin-like growth factor I (IGF-I) within the ovary, which stimulates the synthesis of follicle stimulating hormone receptor (FSHR). Several alternatively spliced transcripts of the FSHR have been identified in sheep. Each variant form is believed to be produced according to the stage of follicle development. This study was carried out to evaluate expression patterns of the FSHR variant forms (FSHR-1, FSHR-2 and FSHR-3) in the sheep ovary in response to different flushing diets. For this experiment, yearling Rambouillet ewes (n=93) were allocated among 6 different energy type treatment diets, either prairie or alfalfa hay based, for at least two weeks in combination with the insertion of a controlled internal drug releasing device (CIDR). Two of the treatment groups had commercially available block supplements provided and two had rolled corn supplemented. Mid-ventral laparotomy was performed on each ewe 3.5 to 4 days after CIDR removal. Follicles 4 mm and greater were aspirated and categorized as either medium (M; 4 to 6 mm) or large (L; > 6 mm). Total RNA was extracted from granulosa cells (GC) and reverse transcribed followed by qPCR of the resulting cDNA using specifically designed primer sets for each variant of the FSHR and for the LH receptor. Changes in live weight were different (P < 0.01) between treatment diets but there were no statistical differences for NEFA concentrations between any of the treatments nor were there differences for body condition (mean = 3.0) or lambing rate. Therefore, it is likely a flushing response did not occur in this study. Expression of FSHR-1was different between M and L follicles (P < 0.01) and tended to be different for ewes fed alfalfa hay (P = 0.05). Overall mean expression of FSHR-3 was greater than expression of FSHR-1 or FSHR-2 (P < 0.01), although there was no difference between M and L follicles, or between treatment diets. The concentration of estradiol in follicular fluid was not different between the treatment diets or follicle sizes nor was expression of lutenizing hormone receptor (LHR), indicating that follicles were similar developmentally. The FSHR-1 form seemed to be the variant most likely to be involved in later stages of follicular development, and is potentially involved in follicle rescue. For all follicles, FSHR-3 was the more highly expressed form of the FSHR and may likely be essential throughout antral follicle development. Further research is required to determine the exact mechanism whereby initial energy status of ewes seems critical for the increased ovulation rate that occurs after energy supplementation (i.e. the flushing response).
Keywords: Follicle; Follicle stimulating hormone receptor variants; Nutritional flushing; Sheep; Animal Sciences (0475)